Evaluation of surface properties of two remineralizing agents after modification by chitosan nano particles: An In vitro study - Dina Mohamed Wahied; Naglaa Ezzeldin; Ali Abdelnabi; Maha Sherif Othman; Mai Hesham Abd El Rahman (Wolters Kluwer Medknow Publications, 2023)
Background: Calcium phosphate-based systems have been introduced as promising bio-mimetic materials due to their close resemblance to the enamel. Chitosan and its derivatives have been an emerging biomaterial due to their additional antibacterial effect and promising re-mineralizing ability. Aim: The aim of this study is to evaluate the effect of chitosan nanoparticles on the remineralization of the demineralized enamel surface after being added to nano-hydroxyapatite and nano-calcium phosphate materials. Setting and Design: This was in vitro study. Materials and Methods: Twenty specimens of extracted permanent molars were collected, and then immersed in demineralizing solution, then distributed into four groups according to the remineralizing material. Group 1: Treated with Nano-beta-tricalcium phosphate (Nβ-TCP) gel, Group 2: Treated with Nβ-TCP with chitosan gel, Group 3: Treated with Nanohydroxyapatite (NHA) gel, and Group 4: Treated with NHA with chitosan gel. The surface hardness of the teeth was measured at baseline, after demineralization, and after remineralization. The structural changes in each group were analyzed using the scanning electron microscopy. Statistical Analysis: Shapiro-Wilk's test, one-way ANOVA followed by Tukey's post hoc test was used. Results: In all groups, there was a significant difference in mean Vickers hardness number (VHN) at different intervals, with the highest value found after treatment (301.64-395.65) VHN, followed by the baseline (236.97-276.15) VHN, while the lowest value was detected after demineralization (121.23-124.39) VHN. It was also indicated that baseline treatment, the Hardness percentage change (%) of the nano NHA + Chitosan group showed the highest significant value (55.10%), while the Nβ-TCP group exhibited the lowest significant value (9.56%). Conclusions: It can be concluded that NHA and NB-TCP modified by chitosan NPs as remineralizing agents of enamel surface hold promising results.